Longitudinal changes in functional connectivity of cortico‐basal ganglia networks in manifests and premanifest huntington's disease. Issue 11 (6th October 2016) - Gargouri, Fatma; Messé, Arnaud; Perlbarg, Vincent; Valabregue, Romain; McColgan, Peter; Yahia‐Cherif, Lydia; Fernandez‐Vidal, Sara; Ben Hamida, Ahmed; Benali, Habib; Tabrizi, Sarah; Durr, Alexandra; Lehéricy, Stéphane
Abstract: Huntington's disease (HD) is a genetic neurological disorder resulting in cognitive and motor impairments. We evaluated the longitudinal changes of functional connectivity in sensorimotor, associative and limbic cortico‐basal ganglia networks. We acquired structural MRI and resting‐state fMRI in three visits one year apart, in 18 adult HD patients, 24 asymptomatic mutation carriers (preHD) and 18 gender‐ and age‐matched healthy volunteers from the TRACK‐HD study. We inferred topological changes in functional connectivity between 182 regions within cortico‐basal ganglia networks using graph theory measures. We found significant differences for global graph theory measures in HD but not in preHD. The average shortest path length ( L ) decreased, which indicated a change toward the random network topology. HD patients also demonstrated increases in degree k, reduced betweeness centrality bc and reduced clustering C . Changes predominated in the sensorimotor network for bc and C and were observed in all circuits for k . Hubs were reduced in preHD and no longer detectable in HD in the sensorimotor and associative networks. Changes in graph theory metrics ( L, k, C and bc ) correlated with four clinical and cognitive measures (symbol digit modalities test, Stroop, Burden and UHDRS). There were no changes in graph theory metrics across sessions, which suggests that these measures are not reliable biomarkers of longitudinal changes in HD. preHD is characterized by progressive decreasing hub organization, and these changes aggravate in HD patients with changes in local metrics. HD is characterized by progressive changes in global network interconnectivity, whose network topology becomes more random over time. Hum Brain Mapp 37:4112–4128, 2016 . ©2016 Wiley Periodicals, Inc.